2003
DOI: 10.1046/j.1365-2443.2003.00646.x
|View full text |Cite
|
Sign up to set email alerts
|

Fate of DNA replication fork encountering a single DNA lesion during oriC plasmid DNA replication in vitro

Abstract: Background : The inhibition of DNA replication fork progression by DNA lesions can lead to cell death or genome instability. However, little is known about how such DNA lesions affect the concurrent synthesis of leading-and lagging-strand DNA catalysed by the protein machinery used in chromosomal replication. Using a system of semi-bidirectional DNA replication of an oriC plasmid that employs purified replicative enzymes and a replication-terminating protein of Escherichia coli , we examined the dynamics of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
133
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(147 citation statements)
references
References 50 publications
(64 reference statements)
14
133
0
Order By: Relevance
“…For this we designed a DNA molecule to mimic the stalled replication fork structure observed most prominently in the limited studies carried out to date in vitro on the structure of forks stalled at leading strand lesions (19,20). Our construct features a long (2035 nucleotide) ssDNA gap on the leading strand (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this we designed a DNA molecule to mimic the stalled replication fork structure observed most prominently in the limited studies carried out to date in vitro on the structure of forks stalled at leading strand lesions (19,20). Our construct features a long (2035 nucleotide) ssDNA gap on the leading strand (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The major stalled fork structure identified in two recent studies is one in which the leading strand has halted DNA synthesis at the site of a lesion, and lagging strand synthesis has continued for some distance (1 kbp or more) beyond that point (19,20). The resulting fork structure has a long single strand gap on the leading strand (Fig.…”
mentioning
confidence: 99%
“…Subsequent work confirmed that sister polymerases are physically attached to one another (1). This colocalization is accompanied by coordination; blocking leading-strand replication stops the whole replisome (3)(4)(5).…”
mentioning
confidence: 86%
“…1E Center). This process is similar to the uncoupling of the leading polymerase in response to blocked laggingstrand replication (4,5). In a third possibility, the independent replisome factory model, there is no coupling between replisomes despite colocalization, and the replisomes may move at different rates (Fig.…”
mentioning
confidence: 89%
“…The observation that the priA mutant undergoes replication fork reversal led us to conclude that the types of replication inactivation that cause replication fork reversal, such as a (34) RecBC, RecA, and RuvABC Replication-dependent linear DNA Overreplication (Fig. 4) UV irradiation (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53) RecFOR and RecA Replication-dependent linear DNA Several models *In replication mutants or strains with ectopic Ter sites, because replication blockage is the only damage, the recombination proteins essential for viability are presumably essential for restart. In UV-irradiated cells, several types of damage occur, and all recombination proteins are required for full viability.…”
Section: Spontaneous Replication Fork Arrest: the Pria Mutantmentioning
confidence: 99%